DASAR-DASAR SOSIOLOGIS DAN ANTROPOLOGIS PENDIDIKAN - Wulan Suhariati; Binti Maunah (LPPM Universitas Widya Dharma, 2024)
Education is a complex phenomenon that cannot be separated from the context of society and culture. Education has several basics that can be used as examples to achieve an educational goal. Because without the basics of education, the goals of education will be difficult to achieve, which can cause education to have unclear goals. One of the basics of education used is sociological and anthropological. Sociological and anthropological foundations are important to understand because they can be used to understand how education works in society and how education can be used to achieve social and cultural goals. And to achieve educational goals, a process of socialization and enculturation needs to be carried out. Apart from that, the educational environment is also needed to support all these processes in formal, informal and non-formal educational environments.